Superfine powdered activated carbon (S-PAC) coatings on microfiltration membranes: Effects of milling time on contaminant removal and flux. (1st September 2016) - Amaral, Pauline; Partlan, Erin; Li, Mengfei; Lapolli, Flavio; Mefford, O. Thompson; Karanfil, Tanju; Ladner, David A.
Abstract: In microfiltration processes for drinking water treatment, one method of removing trace contaminants is to add powdered activated carbon (PAC). Recently, a version of PAC called superfine PAC (S-PAC) has been under development. S-PAC has a smaller particle size and thus faster adsorption kinetics than conventionally sized PAC. Membrane coating performance of various S-PAC samples was evaluated by measuring adsorption of atrazine, a model micropollutant. S-PACs were created in-house from PACs of three different materials: coal, wood, and coconut shell. Milling time was varied to produce S-PACs pulverized with different amounts of energy. These had different particles sizes, but other properties (e.g. oxygen content), also differed. In pure water the coal based S-PACs showed superior atrazine adsorption; all milled carbons had over 90% removal while the PAC had only 45% removal. With addition of calcium and/or NOM, removal rates decreased, but milled carbons still removed more atrazine than PAC. Oxygen content and specific external surface area (both of which increased with longer milling times) were the most significant predictors of atrazine removal. S-PAC coatings resulted in loss of filtration flux compared to an uncoated membrane and smaller particles caused more flux decline than larger particles; however, the data suggest that NOM fouling is still more of a concern than S-PAC fouling. The addition of calcium improved the flux, especially for the longer-milled carbons. Overall the data show that when milling S-PAC with different levels of energy there is a tradeoff: smaller particles adsorb contaminants better, but cause greater flux decline. Fortunately, an acceptable balance may be possible; for example, in these experiments the coal-based S-PAC after 30 min of milling achieved a fairly high atrazine removal (overall 80%) with a fairly low flux reduction (under 30%) even in the presence of NOM. This suggests that relatively short duration (low energy) milling is viable for creating useful S-PAC materials applied in tandem with microfiltration. Graphical abstract: Highlights: Activated carbon milled to superfine sizes was used with microfiltration membranes. Water quality (organic matter, calcium, etc.) effects were evaluated. Milling time affected the S-PAC efficiency for atrazine removal. Specific external surface area most strongly correlated with atrazine removal. Milling times that optimized flux and atrazine removal were relatively short.